An Assistance in Preparing the TPQ Curriculum Based on Religious Moderation at Nurul Iman Mosque - Aisyah Khumairo; Shely Nasya Putri; Suhono, Suhono (International Journal of Community Engagement Payungi, 2023)
Religious moderation is an attitude that must be instilled in young people from an early age. One way that can be used to instill the value of religious moderation from an early age is through the curriculum in formal and non-formal education. In this mentoring activity, the inculcation of the value of religious moderation is injected into the curriculum at TPQ (Taman Pendidikan Al-Quran) which is one of the non-formal religious institutions. The purpose of this mentoring activity is to provide an understanding of the importance of the religious moderation curriculum. In addition, this activity also aims to provide assistance in making the TPQ curriculum based on religious moderation at TPA Nurul Iman Tejoagung. The method used ABCD (Asset Based Community Development), which prioritizes the utilization of assets and potentials that are around and owned by the TPA Nurul Iman. All stages of this mentoring activity have been running well and have received support from related parties.